Assessment of Duration of Tick Feeding by the Scutal Index Reduces Need for Antibiotic Prophylaxis After Ixodes scapularis Tick Bites. (20th March 2018) - Falco, Richard C; Daniels, Thomas J; Vinci, Vanessa; McKenna, Donna; Scavarda, Carol; Wormser, Gary P
Abstract: Doxycycline is recommended for persons with Ixodes scapularis tick bites in certain geographic areas, if the tick had fed for at least 36 hours. Based on the scutal index, over 40% of I. scapularis tick bites from patients seen at the Lyme Disease Diagnostic Center did not warrant antibiotic prophylaxis.